Inequality in Mexico - Prát, Šárka; Chvalkovská, Jana; Inostroza Pino, Luis; Vysoká škola ekonomická v Praze. Národohospodářská fakulta (2013)
This thesis project has the aim of analysing the development of inequality in Mexico, income redistribution, and future possibilities of investment into the educational system. Human capital is one of the determinants of economic growth. Although human capital includes health, education, and social capital, the major focus of this diploma thesis is on education. Education becomes a suitability criterion for employment in all sectors of industry. Everyone is rewarded for exercising the knowledge required for the field they venture, and evaluated on the market on the basis of their educational skills and how well he can apply them. Good education offers a better opportunity to get a job. Strategic analysis and research development shows that an increase in the level of education leads to access to higher wages, which, in turn, lowers the poverty rate. Mexico must increase its investment in education, especially high schools, if it is to address its high poverty rate. The social inequality in Mexico is way beyond levels of inequality observed in other countries with a similar level of development. This thesis additionally includes the comparison of Mexico to Argentina and Brazil (countries of similar size and importance within the Latin American region). Finally the last section presents conclusions and final recommendations.
Vedoucí práce: Jana Chvalkovská
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Národohospodářská fakulta, 2013
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2013
Způsob přístupu: Internet
Keywords: ekonomická a regionální studia latinské ameriky [obor dipl. práce]; diplomové práce; master's theses